Comparative analysis of emergency department patients lost to follow-up after computerized alcohol screening and brief intervention. Issue 5 (4th July 2018) - Hosseini Farahabadi, Maryam; Chakravarthy, Bharath; Hoonpongsimanont, Wirachin; Vaca, Federico E.; McCoy, Christopher E.; Anderson, Craig L.; Imani, Ghasem; Wong, Priscilla; Lotfipour, Shahram
ABSTRACT: Many studies have evaluated the effectiveness of alcohol screening and brief intervention (SBI) but most of them have reported substantial loss to follow-up without investigating the characteristics of those lost to follow-up. We examined the association between Alcohol Use Disorders Identification Test (AUDIT) scores, readiness-to-change scores and the demographic factors with lost to follow-up. This retrospective study compared demographic characteristics, AUDIT and readiness-to-change scores for 190 lost to follow-up patients to 221 completed follow-up patients who participated in SBI in the Emergency Department between June 2006 and May 2007. Comparing the association between baseline characteristics and completed follow-up rate, those 30–39, 40–49 and 50 years and older had 0.46 (95% CI 0.32–0.91), 0.49 (95% CI 0.29–0.90) and 0.58 (95%CI 0.22–0.79) lower odds of completing follow-up, respectively, in comparison to those 18–29 years of age. The loss to follow-up group reported more negative consequences of alcohol and binge drinking than the completed follow-up group (p = 0.04). Using logistic regression, patients who experienced more negative effects of alcohol had 0.87 lower odds of completing follow-up (95% CI 0.79–0.96). The patients lost to follow-up in this study were significantly different in age and alcohol drinking habits compared to those completed follow-ups. It is important to consider differential loss to follow-up in assessing the validity and generalizability of intervention studies. This could help in tailoring methods of approaching patients based on target population characteristics.